A Quantitative Approach for Web Usability using Eye Tracking Data - LÓPEZ-OROZCO, Francisco (IntechOpen, 2018)
https://www.intechopen.com/books/artificial-intelligence-emerging-trends-and-applications/a-quantitative-approach-for-web-usability-using-eye-tracking-data